Implication of Fuel Subsidy Removal on Household Nutrition and Health Status in Kogi Central Senatorial District of Kogi State - Tioluwa Justina Atiti; Calister Lebechukwu Nwadi; Domitila Ogechi Emesiani; Rachael Adiya Wonah (International Journal of Home Economics, Hospitality and Allied Research)
This study examined the implication of fuel subsidy removal on household nutrition and health status in Kogi Central. Four research questions were stated for the study. The design used was survey and the population comprise all household in Okehi Local Government Area of Kogi State. From the communities in the area, Otite-Eika Adagu was selected. The simple random sampling technique was used to select one hundred households. The instrument for data collection was a questionnaire titled Implication of Fuel Subsidy Removal on the Household Nutrition and Health Status (IFSRHNHS). It was designed on a three point scaling of Aware, undecided and Not aware for research question one and Always, Sometimes and Never for the remaining research questions. The instruments were subjected to face and content validity by a lecturer and a Nurse. Its reliability was established by administering them on households outside the area of study using the split half method. The Pearson Product Moment Correlation Coefficient yielded 0.69. From the administered one hundred questionnaire to households, eighty one were collected. The data generated were analyzed using percentage (%) and the study adopted 50% for taking decisions. The study implicates an unfriendly dietary intake in the post-subsidy removal era. The work concluded that households were aware that poor feeding habit causes common and life-threatening health issues. It recommended among others that, the federal government of Nigeria should rethink the framework and implementation of its present policy on the removal of fuel subsidy.